Implementasi Keterlibatan Masyarakat dalam Proses Pembuatan AMDAL Kegiatan Pertambangan di Sulawesi Tenggara (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This research examines the legal issues surrounding the Environmental Impact Assessment (Analisis Mengenai Dampak Lingkungan—AMDAL) as a prerequisite for obtaining business or activity permits in Indonesia. The study adopts a normative juridical approach, analyzing legal theories, concepts, and principles relevant to environmental law. The enactment of Law Number 11 of 2020 on Job Creation introduced significant amendments, deletions, and new provisions to Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law). One of the most substantial changes is the removal of the explicit obligation to obtain an environmental permit, replacing it with a requirement for environmental approval issued by the central government. This environmental approval consists of the Statement of Environmental Management Capability (Pernyataan Kesanggupan Pengelolaan Lingkungan Hidup—PKLHP) and the Environmental Feasibility Decision (Keputusan Kelayakan Lingkungan Hidup—KKLH), both intended to ensure that businesses and activities comply with environmental standards before commencing operations. However, the revision also affects public participation in the AMDAL process. Under the Job Creation Law, opportunities for environmental organizations and local communities to be involved in the preparation, review, and decision-making stages of AMDAL have been significantly reduced. This shift raises concerns about transparency, accountability, and the integration of environmental, social, and economic considerations in decision-making. In the context of sustainable development, environmental permits or approvals should not only serve as administrative formalities but also as instruments to safeguard environmental quality and uphold public interest. Public participation plays a critical role in ensuring that AMDAL processes reflect diverse perspectives, promote environmental justice, and support the long-term goals of environmental protection. The study concludes that while the Job Creation Law aims to streamline licensing and promote investment, its impact on public involvement in environmental governance poses risks to the integrity of environmental protection frameworks in Indonesia.